Organização da Instrução na Província de Minas Gerais : da legislação aos relatórios dos presidentes (1850-1889) - Andrade, Renata Fernandes Maia de (2007)
The aim of this work is to analyze the development of the instruction in the Province of Minas Gerais between 1580 and 1889. We intend to understand the objectives and intentions that orientated the school organization in the mining province, which were the financial resources used for the maintenance of the schools, as well what kind of individual was supposed to be formed through education. The initial period of our study was delimited taken into consideration the consolidation of the political-administrative unit capable to overcome the rebellions occurred at the end of the mid 19th century. We established as a final historical mark of our work the fall of the Monarchic regime in 1889. As a main research source we used the educational legislation and the Province President s Reports produced during the period mentioned above. It is from this data that we arrived at the conceptions of education, progress and civilization in the mining society. During the Imperial period in Minas Gerais, learning processes of reading and writing were linked to the moral instruction. Major elite will consider this as a creation mean of new social practices. The speeches demonstrate that instruction was considered a fundamental way to civilize and to impose moral conceptions on the population. However, during the period here investigated, we observed a lack of continuity of the proposals that intended to reform and to restructure the mining education in the late 19th century.